Investigation Of Antioxidants, Antidiabetic And Antihyperlipidemic Activity Of Vitex Trifolia Seeds In Diabetic Zebrafish Model (Journal of Pharmaceutical Negative Results, 2023)
Diabetes and obesity are now regarded as global epidemics. Researchers coined the term "diabesity" to describe the relationship between these two diseases as obesity and diabetes rates rise simultaneously. Type 2 diabetes mellitus, heart disease, and numerous types of cancer are all made more likely by obesity. Diabetes and obesity are two examples of complex diseases that are influenced by both hereditary and environmental factors. Due to the lack of knowledge regarding the underlying pathophysiology of obesity and diabetes, additional research is needed before pharmacological and surgical treatments can be used. Therefore, it is essential to use animal models of diabetes and/or obesity to advance our understanding of these conditions as well as to find and create efficient treatments for them. Zebrafish is a desirable model system for studying metabolic diseases due to functional conservation in lipid metabolism, adipose biology, pancreas structure, and glucose homeostasis. Finding new approaches to prevent and treat human diseases like diabetes and obesity is a good fit for it. This review discusses the advantages and disadvantages of using zebrafish as a model to study the pathologies associated with obesity and diabetes. It focuses on studies that have used zebrafish as a model for these diseases.